The effects of delayed school start on Icelandic adolescents' sleep duration and sleep quality - Ása María Ásgeirsdóttir 1998- (2022)
For the last 20 years, sleep among adolescents has decreased, and previous studies have shown that seven out of ten high schoolers do not get enough sleep, particularly not on school nights. Recent studies have examined the effects delayed school starts can have on adolescent sleep patterns. This current study aimed to examine the effects of delayed school start on Icelandic adolescents' sleep duration and sleep quality. Participants were students from two elementary schools in Reykjavík, Víkurskóli (N = 144), and Foldaskóli (N = 143), ranging from the age of 13-16. School started at 8:40 in Víkurskóli and 8:10 in Foldaskóli. The study was a mixed-method study, and its design was an embedded design. The quantitative data was collected with a questionnaire from Skólapúlsinn, and the qualitative data was gathered with a focus group discussion. The study was based primarily on the quantitative data, and the qualitative data was used to provide a supportive, secondary role. The study’s main result was that participants from Víkurskóli got significantly more sleep than participants from Foldaskóli, t(276) = -2.34, p = .020, indicating that delaying school start does increase adolescents' sleep duration. This is the first study of its kind that is conducted in Iceland. Keywords: Delayed school schedule, sleep quality, sleep duration, adolescents Síðastliðin 20 ár hefur svefn meðal unglinga farið minnkandi og hafa fyrri rannsóknir sýnt að sjö af hverjum tíu framhaldsskólanemendum sofa ekki nægilega mikið, þá sérstaklega ekki á virkum dögum. Nýlegar rannsóknir hafa kannað áhrif seinkaðar skólabyrjunar á svefn unglinga. Þessi rannsókn miðaði að því að kanna hvaða áhrif seinkuð skólabyrjun hefur á svefngæði og svefnlengd íslenskra unglinga. Þátttakendur voru nemendur úr tveimur grunnskólum í Reykjavík, Víkurskóla (N = 144) og Foldaskóla (N = 143), á aldrinum 13-16 ára. Skóli hófst klukkan 8:40 í Víkurskóla og 8:10 í Foldaskóla. Í rannsókninni voru bæði notaðar megindlegar og eigindlegar mælingar. Megindlegu gögnunum var ...